2014
DOI: 10.4314/ejesm.v7i1.10s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pattern of Inter-Urban Travels of Public Transport Passengers in Lagos Metropolis

Abstract: This study assessed the pattern of inter-urban travels of public transport passengers in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Studies abound on rail transport services, such as their operation and patronage. These studies include Agunloye and Ilechukwu [1], Irfan et al [11], Odufuwa [17], Olayiwola et al [20], Olojede [23], Olojede et al [27], Oni and Okanlawon [29], and Salkonen and Paavilainen [34]. However, most of these studies did not get to assessing empirically established indicators of passengers' satisfaction with the services provided by rail transport.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies abound on rail transport services, such as their operation and patronage. These studies include Agunloye and Ilechukwu [1], Irfan et al [11], Odufuwa [17], Olayiwola et al [20], Olojede [23], Olojede et al [27], Oni and Okanlawon [29], and Salkonen and Paavilainen [34]. However, most of these studies did not get to assessing empirically established indicators of passengers' satisfaction with the services provided by rail transport.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Specifically, Agunloye and Ilechukwu [1] examined the travel pattern and socioeconomic characteristics of rail transport passengers in Lagos Metropolis, Nigeria. The findings from the study revealed that most passengers were low-income earners, engaged in work-related trips, and made more trips per week because they depended highly on trains than any other mode.…”
Section: Previous Studiesmentioning
confidence: 99%
“…For many years, public transport has been viewed as an inevitable need in several parts of the world (Cervero & Golub,2007). Transport is also the key player in the transfer and distribution of goods from the input points through the manufacturing line to the customer (Agunloye, 2011) perhaps, this led to the assertion by Badejo (2002), that there is no escape from public transportation since it is a key stone of civilization. No wander a study in the area of public transportation indicated that more than 75% of population in cities depends on public transport while 25% depends on private transport (Ogunbodede,1990).…”
Section: Introductionmentioning
confidence: 99%